Mouse Mast Cell Protease 4 Deletion Protects Heart Function and Survival After Permanent Myocardial Infarction - Houde, Martin; Schwertani, Adel; Touil, Hanène; Desbiens, Louisane; Sarrhini, Otman; Lecomte, Roger; Lepage, Martin; Gagnon, Hugo; Takai, Shinji; Pejler, Gunnar; Jacques, Danielle; Gobeil, Fernand; et al. (Frontiers in Pharmacology, 2018)
Chymase, a mast cell serine protease involved in the generation of multiple cardiovascular factors such as angiotensin II and endothelin-1 (ET-1), is elevated and participates in tissue degeneration after permanent myocardial infarction (PMI). Anaesthetized four-month old male wild-type (WT) C57BL/6J mice and mouse mast cell protease-4 knockout (mMCP-4 KO) congeners were subjected to ligation of the left anterior descending (LAD) coronary artery. A group of mice was then subjected to Kaplan-Meier 28-day survival analysis. In another group of mice, 18F fluorodeoxyglucose positron emission tomography (PET) was performed to evaluate heart function and the infarcted zone 3 days post-PMI surgery. Cardiac morphology following PMI was evaluated on formalin-fixed heart slices and glycoproteomic analysis was performed using mass spectrometry. Finally, cardiac and lung tissue content of immunoreactive ET-1 was determined. PMI caused 60 % mortality in WT mice due to left ventricular wall rupture, and 7 % in mMCP-4 KO mice. Cardiac PET analysis revealed a significant reduction in left ventricular volume (systolic and diastolic) and preserved the ejection fraction in mMCP-4 KO compared to WT animals. The infarcted area, apoptotic signaling and wall remodeling were significantly decreased in mMCP 4 KO mice compared to their WT congeners, while collagen deposition was increased. Glycoproteomic analysis showed an increase in apolipoprotein A1, an established chymase substrate in mMCP-4 KO mice compared to WT mice post-PMI. Endothelin 1 levels were increased in the lungs of WT, but not mMCP-4 KO mice, 24 h post-PMI. Thus, the genetic deletion of mMCP-4 improved survival and heart function post-PMI.